PENGARUH RASIO KEUANGAN TERHADAP NILAI Z-SCORE SEBAGAI PREDIKSI FINANCIAL DISTRESS (Studi Kasus Pada Perusahaan Jasa Sektor Hotel Restoran dan Pariwisata yang Tercatat di Bursa Efek Indonesia Periode 2016-2020) - paozi, vanih (Journal of Fundamental Management (JFM), 2023)
This study aims to determine the effect of financial rations which are Working Capital to Total Asset (WCTA), Retained Earnings to Total Asset (RETA), Ebit to Total Asset (EBITTA), dan Debt to Equity Ratio (DER) on Z-Score as a prediction of financial distress. The population in this study are hotel, restaurant, and tourism sector services companies listed on the Indonesia Stock Exchange in 2016-2020 which reveal 11 companies according to the characteristics set by the researcher. The sample selection used the saturated sample method and obtained 10 companies. The data collection method uses triangular data, using data from the company's annual financial statements obtained from the Indonesia Stock Exchange (IDX) website and the websites of each company. The research method is causality research with data analysis method using panel data regression analysis with the chosen approach model, namely the common effect model. The results showed that Working Capital to Total Asset (WCTA), Retained Earnings to Total Asset (RETA), Ebit to Total Asset (EBITTA), dan Debt to Equity Ratio (DER) has a positive and significant effect on Z-Score as a prediction of financial distress in hotel, restaurant, and tourism sector services companies.